2014
DOI: 10.1002/adfm.201402692
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures and Photoconversion Mechanism in Perovskite/Fullerene Heterojunctions

Abstract: It has been generally believed and assumed that organometal halide perovskites would form type II P–N junctions with fullerene derivatives (C60 or PCBM), and the P–N junctions would provide driving force for exciton dissociation in perovskite‐based solar cell. To the best of our knowledge, there is so far no experiment proof on this assumption. On the other hand, whether photogenerated excitons can intrinsically dissociate into free carrier in the perovskite without any assistance from a P–N junction is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 41 publications
10
79
1
Order By: Relevance
“…With increasing C 60 coverage, an upward bending of the transport levels by 800 meV occurs accompanied by an upward shift of the perovskite DOS, indicating an electron transfer into the C 60 layer. Third, Lo et al 20 observed in their UPS measurements a staggered interface as shown in Fig. 6(c), so the LUMO of C 60 at the interface is positioned 340 meV above the perovskite CB, leading to an extraction barrier of 340 meV while the HOMO is below the VB of the perovskite, so no hole blocking should be achieved.…”
Section: Energetic Alignment To Organic Transport Layersmentioning
confidence: 97%
“…With increasing C 60 coverage, an upward bending of the transport levels by 800 meV occurs accompanied by an upward shift of the perovskite DOS, indicating an electron transfer into the C 60 layer. Third, Lo et al 20 observed in their UPS measurements a staggered interface as shown in Fig. 6(c), so the LUMO of C 60 at the interface is positioned 340 meV above the perovskite CB, leading to an extraction barrier of 340 meV while the HOMO is below the VB of the perovskite, so no hole blocking should be achieved.…”
Section: Energetic Alignment To Organic Transport Layersmentioning
confidence: 97%
“…14 However, there is so far little studies probing the chemical nature of the ions and how these ions pay their role in the photocharge generation. 3,15 Organometal trihalide perovskites have properties differ considerably from their constituting components. [16][17] For example, MAI and PbCl 2 are themselves wide energy gap semiconductors and therefore are electrically and optically inert.…”
Section: Introductionmentioning
confidence: 99%
“…The initial pH value of the solution was adjusted using 0.1 M NaOH or HNO 3 . All experiments were carried out under constant stirring to ensure well dispersion of the samples.…”
Section: Photocatalytic Tests and Analytical Methodsmentioning
confidence: 99%
“…Fh was prepared by slowly and simultaneously titrating Fe(NO 3 ) 3 (1 M, 40 mL) and NaOH (6 M, 20 mL) into 10 mL ultrapure water, with vigorous magnetic stirring and controlling the solution pH at 7 ± 0.2. After continuous magnetic stirring for another 30 min, the products were centrifuged and washed.…”
Section: Preparation Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation